1989
DOI: 10.1002/1097-0142(19890401)63:7<1388::aid-cncr2820630725>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and cadmium concentrations in indigenous blacks with normal, hypertrophic, and malignant prostate

Abstract: In order to determine the role of cadmium and zinc in the very low incidence (10/100,000) of cancer of the prostate, in African blacks which contrasts with the very high incidence (100/100,000) in American blacks, the authors measured the serum and prostatic concentrations of these trace metals in healthy Nigerian men and those with benign prostatic hypertrophy (BPH) and prostatic cancer using atomic absorption spectrophotometric study. The mean plasma zinc concentration of healthy men was 14.9 mumol/l +/- 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
1
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(76 citation statements)
references
References 24 publications
6
67
1
2
Order By: Relevance
“…These parameters demonstrate that the extra ZBP does not alter much of the intrinsic zinc-binding of endostatin. Although the concentrations of plasma zinc and tissue zinc vary in people at different ages or suffering from different tumors (44,45), zinc is one of the most abundant trace metals in normal people with an average plasma concentration around 14.9 lM (45). Therefore, both endostatin and ZBP-endostatin should be predominantly in the zinc-bound form under physiological conditions.…”
Section: Contribution Of Zinc Ion To the Structural Stability And Biomentioning
confidence: 99%
“…These parameters demonstrate that the extra ZBP does not alter much of the intrinsic zinc-binding of endostatin. Although the concentrations of plasma zinc and tissue zinc vary in people at different ages or suffering from different tumors (44,45), zinc is one of the most abundant trace metals in normal people with an average plasma concentration around 14.9 lM (45). Therefore, both endostatin and ZBP-endostatin should be predominantly in the zinc-bound form under physiological conditions.…”
Section: Contribution Of Zinc Ion To the Structural Stability And Biomentioning
confidence: 99%
“…In the lateral lobe, the concentration of MT in group 4 was low compared with those in groups 2 and 3, possibly due to dysfunction of prostatic cells following administration of a high dose. Cadmium inhibits the uptake of zinc by the prostate and decreases the intracellular zinc content (Ogunlewe and Osegbe 1989). The prostate contains many enzymes such as acid phosphatase and 5a-reductase which need zinc (Mawson and Fischer 1952b ;bare et al 1956bare et al Vallee 1959Ogunlewe and Osegbe 1989).…”
Section: Resultsmentioning
confidence: 76%
“…Zinc concentration is high in prostatic tissue and fluid (Mawson and Fischer 1952a;Gyorkey et al 1967 ;Anderson and Fair 1976;Ogunlewe et al 1989), and the concentration of zinc has been found to affect male infertility (Anderson et al 1976). This shows MT of the prostate binds to zinc.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The trace element contents in tissue of the normal and cancerous prostate have been studied, producing contradictory results (Tipton et al, 1954;Koch & Smith, 1956;Stitch, 1957;Tipton & Cook, 1963;Sangen, 1967;Weinig & Zink, 1967;Liebscher & Smith, 1968;Höffken & Rausch-Stroomann, 1969;Soman et al, 1970;Forssen, 1972;Dhar et al, 1973;Kubo et al, 1976;Jafa et al, 1980;Ogunlewe & Osegbe, 1989;Oldereid et al, 1993;Banaś et al, 2001;Kwiatek et al, 2001;Kwiatek et al, 2004;Eckhert, 2005;Galván-Bobadilla et al, 2005;Kwiatek et al, 2005;Yaman et al, 2005;Guntupalli et al, 2007;Muecke et al, 2009;Kiziler et al, 2010;Schöpfer et al, 2010;Guzel et al, 2012;Leitão et al, 2014;Neslund-Dudas et al, 2014). The majority of these data are based on measurements of processed tissue and in many studies tissue samples are digested before analysis.…”
Section: Introductionmentioning
confidence: 99%